The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s10895-013-1251-5
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Fluorescent Sensor Based on 1H-pyrazolo[3,4-b]quinoline in Analytical Chemistry

Abstract: Fluorescent dye 2-[(2-Hydroxyethyl)-(1,3-diphenyl-1H-pyrazolo[3,4-b]quinolin-6-ylmethyl)-amino]ethanol (LL1) was examined for its efficiency in the detection of small inorganic cations (lithium, sodium, barium, calcium, magnesium, cadmium, lead and zinc). The dye was synthesized in the laboratory and investigated by means of both, steady-state and time-resolved fluorescence techniques. This compound acts as a fluorescent sensor suitable for detection of small inorganic cations (lithium, sodium, barium, calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…5 and Table S4, ESI †). The torsion angles (Table S5, ESI †) of C(17), C (18), C(20), N(2) and N(3) are zero, which prove the presence of these atoms in one ring system. 11) are very small.…”
Section: Crystal Structure Of Dpqmentioning
confidence: 91%
See 1 more Smart Citation
“…5 and Table S4, ESI †). The torsion angles (Table S5, ESI †) of C(17), C (18), C(20), N(2) and N(3) are zero, which prove the presence of these atoms in one ring system. 11) are very small.…”
Section: Crystal Structure Of Dpqmentioning
confidence: 91%
“…Generally, an ideal G-quadruplex fluorescent probe is assumed to consist of a fluorescent signaling unit specifically recognizing the G-quadruplex structure. Pyrazoloquinolines have been shown to be efficient organic emitters, [16][17][18] with applications in fluorescence sensing 19,20 and electroluminescence. 21 Recently, a derivative of this class of compounds showed a selective binding to human telomeric G4 multimers over monomeric ones.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that this compound can act as a highly efficient Since the aforementioned studies on pyrazoloquinoline-based sensors were reported, almost a decade passed until this stem was followed. Then, between 2010 and 2013, Mac and co-workers published a series of articles on ion-sensitive pyrazoloquinolines, which varied by the molecular architecture of the receptor unit (see Figure 16b) [175][176][177]. All of the sensors presented (PQ 1a-d) were designed for PET signalling, and they maintained the connection between the receptor unit and the pyrazoloquinoline chromophore via the non-conjugated methylene spacer.…”
Section: Application Of Pyrazoloquinolines In Fluorescence Sensingmentioning
confidence: 99%
“…As a class of important quinoline derivatives, pyrazolo [3,4-b]quinoline derivatives have potential antiviral, [5] antimalarial, [6] and serum cholesterol lowering activities, [7] and blue luminescence properties. [8] In consideration of the above potential application prospects of pyrazolo [3,4-b]quinoline derivatives, their synthesis is always a research hotspot in organic synthetic chemistry. In the reported literatures, the most common synthesis method is the condensation of aldehydes with 1,3-dicarbonyl compounds and aminopyrazole in organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that they exhibited potential antiviral, [2] antimalarial, [3] and anti‐inflammatory [4] properties. As a class of important quinoline derivatives, pyrazolo[3,4‐b]quinoline derivatives have potential antiviral, [5] antimalarial, [6] and serum cholesterol lowering activities, [7] and blue luminescence properties [8] . In consideration of the above potential application prospects of pyrazolo[3,4‐ b ]quinoline derivatives, their synthesis is always a research hotspot in organic synthetic chemistry.…”
Section: Introductionmentioning
confidence: 99%